2015
DOI: 10.1002/cta.2117
|View full text |Cite
|
Sign up to set email alerts
|

Design of a ZVS PWM DC–DC converter for high gain applications

Abstract: SUMMARYIn this paper, a pulse width modulation DC-DC converter with high step-up voltage gain is proposed. The proposed converter achieves high step-up voltage gain with appropriate duty ratio, coupled inductor, and voltage multiplier technique. The energy stored in the leakage inductor of the coupled inductor can be recycled in the proposed converter. Moreover, because both main and auxiliary switches can be turned on with zero-voltage switching, switching loss can be reduced by soft-switching technique. So t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Some features of the proposed converter and similar converters presented in previous studies 11,22,23,[25][26][27][28][29]35,37 are indicated in Table 1. Some features of the proposed converter and similar converters presented in previous studies 11,22,23,[25][26][27][28][29]35,37 are indicated in Table 1.…”
Section: Comparison Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Some features of the proposed converter and similar converters presented in previous studies 11,22,23,[25][26][27][28][29]35,37 are indicated in Table 1. Some features of the proposed converter and similar converters presented in previous studies 11,22,23,[25][26][27][28][29]35,37 are indicated in Table 1.…”
Section: Comparison Studymentioning
confidence: 99%
“…Using the inductor volt-second balance law for the magnetizing inductance, L m , the following equation is achieved: Therefore, the voltage across capacitor C 1 is achieved as given in (11).…”
Section: Ccm Operationmentioning
confidence: 99%
“…where I m21 is the current value of i Lm2 at the moment t 3 . The input current during this mode is obtained as i ℓ = i ℓ1 + i ℓ2 = i Lm1 + i Lm2 from (4) and (13). Based on the equivalent circuit and by applying KVL in phase 1, the voltage stress on switch S 1 can be calculated as follows:…”
Section: Boost Operating Statementioning
confidence: 99%
“…Multi‐level supply voltage feasibility is strictly demanded for nowadays modern electronic devices which require different voltage levels within a unique system on chip (SoC), to achieve optimum overall performance depending on the frequency of operation, connected load, and required processing complexity . Hence designing low‐power high‐efficiency DC‐DC buck converter circuits which can produce the appropriate voltages for proper functionality of the electronic circuits and systems are severely indispensable .…”
Section: Introductionmentioning
confidence: 99%